2016
DOI: 10.1002/ange.201607188
|View full text |Cite
|
Sign up to set email alerts
|

Butelase‐Mediated Macrocyclization of d‐Amino‐Acid‐Containing Peptides

Abstract: Macrocyclic compounds have received increasing attention in recent years. With their large surface area, they hold promise for inhibiting protein–protein interactions, a chemical space that was thought to be undruggable. Although many chemical methods have been developed for peptide macrocyclization, enzymatic methods have emerged as a promising new economical approach. Thus far, most enzymes have been shown to act on l‐peptides; their ability to cyclize d‐amino‐acid‐containing peptides has rarely been documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…It was found that kB1 and SFIT‐1 can be cyclized by butelase 1 with excellent efficiency (>95% yeild) 183 . Butelase 1 has a broad application as it could also recognize and cyclize peptide with nonnatural amino acids such as (N14)‐D‐SFTI‐1 184 . Similarly, OaAEP1b was shown to generate bioactive kB1 effectively 25,180 .…”
Section: Transforming Plant Cyclic Peptide Production and Drug Development With Insights Gained From Their Biosynthesismentioning
confidence: 99%
“…It was found that kB1 and SFIT‐1 can be cyclized by butelase 1 with excellent efficiency (>95% yeild) 183 . Butelase 1 has a broad application as it could also recognize and cyclize peptide with nonnatural amino acids such as (N14)‐D‐SFTI‐1 184 . Similarly, OaAEP1b was shown to generate bioactive kB1 effectively 25,180 .…”
Section: Transforming Plant Cyclic Peptide Production and Drug Development With Insights Gained From Their Biosynthesismentioning
confidence: 99%
“…Given the considerable interest in developing efficient macrocyclizing enzymes as tools for producing highly stable bioactive molecules, butelase 1, the most efficient native cyclizing AEP known to date, has attracted a great deal of attention (Nguyen et al ., , ,b; Bi et al ., ). However, the practicality of butelase 1 as a tool for synthetic production of cyclic peptides has been limited by an inability to produce it as a recombinant protein (Nguyen et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Homology‐based modelling of Butelase 1 suggested that a putative extended C‐terminal domain could contribute to its ligase activity by binding the cleaved substrate at the active site and protecting the acyl intermediate from hydrolysis in a similar manner to PatG, a cyanobacterial serine protease capable of cyclization (Koehnke et al ., ; Nguyen et al ., ). The C. ternatea‐ extracted AEP was highly efficient and has been subsequently used to cyclize or ligate an impressive host of non‐native targets (Nguyen et al ., , ,b; Hemu et al ., ); however, attempts by Nguyen et al . () to generate recombinant protein failed, limiting its potential for commercial use.…”
Section: Plant Aeps With Macrocyclizing Abilitymentioning
confidence: 99%